CD1-restricted T cells: are unconventional allies the key to future TB vaccines? - Milton, Matthew; Mansour, Salah (Frontiers in Immunology, 2025)
CD1-restricted T cells constitute an unconventional arm of immunity that recognises lipid antigens, a feature particularly pertinent to Mycobacterium tuberculosis (Mtb), a pathogen with a lipid-rich cell wall. Unlike classical MHC-restricted responses, CD1-mediated lipid antigen presentation includes donor-unrestricted T cell responses, offering a promising pathway for universally protective tuberculosis (TB) vaccines. This review explores the biology of CD1 isoforms, the functional diversity of CD1-restricted T cell subsets, and their roles in TB immunity. We discuss Mtb’s lipid antigens, mechanisms of CD1 trafficking and antigen presentation, immune evasion strategies, and emerging translational insights. By highlighting key knowledge gaps and future directions, we argue that harnessing CD1-restricted T cells could unlock novel vaccine strategies against the world’s leading infectious killer.